2000
DOI: 10.1088/0022-3727/33/11/309
|View full text |Cite
|
Sign up to set email alerts
|

Atomic oxygen recombination on fused silica: modelling and comparison to low-temperature experiments (300 K)*

Abstract: This work is devoted to the study of atomic oxygen recombination on a glass surface, mainly in connection with atomic sources development. In this paper we present a non-stationary model for atomic oxygen recombination on a fused silica surface. Kinetics equations for oxygen atoms, taking into account heterogeneous reactions between gaseous atoms and the surface (Eley-Rideal mechanisms), as well as homogeneous processes involving surface migration of adsorbed species (Langmuir-Hinshelwood mechanisms), are solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 22 publications
12
80
1
Order By: Relevance
“…Due to the complex nature of the dielectric surface, it is difficult to compute the probability for even such ''simple'' reactions at atom recombination. However, based on the references about heterogeneous reactions of the recombination of O radicals and the combination of CO with O radicals, it is suggested that the formation of O 2 molecules prevails over the combination of CO and O radicals on solid surfaces [24,34,35]. The positive role of solid surfaces provided by dielectric pellets was further confirmed in ''Influence of the Discharge Length on the Decomposition of CO 2 ''.…”
Section: Resultsmentioning
confidence: 98%
“…Due to the complex nature of the dielectric surface, it is difficult to compute the probability for even such ''simple'' reactions at atom recombination. However, based on the references about heterogeneous reactions of the recombination of O radicals and the combination of CO with O radicals, it is suggested that the formation of O 2 molecules prevails over the combination of CO and O radicals on solid surfaces [24,34,35]. The positive role of solid surfaces provided by dielectric pellets was further confirmed in ''Influence of the Discharge Length on the Decomposition of CO 2 ''.…”
Section: Resultsmentioning
confidence: 98%
“…The discharge vessel is a cylinder with the length of 400 mm and the diameter of 40 mm, made from a borosilicate glass with a low recombination coefficient for reaction O + O ! O 2 [12][13][14]. On one side, it is pumped with the vacuum pump with the nominal pumping speed of 16 m 3 /h, while on the other side commercially available oxygen is leaked through a precise leak valve.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Well stirred reactors are characterised by constant reactor volume, mass flow rate, surface area, inlet composition and temperature, as well as the power induced into the plasma for non-thermal systems. Most of the contributing parameters were determined from the literature [21][22][23][24][25][26][27] and the experimental results.…”
Section: Simulation Of the Oxygen Atom Recombination On Oxide Semiconmentioning
confidence: 99%